LOBECTOMIA PULMONAR EM CANINO: RELATO DE CASO - de Cezaro, Tainara; Farret, Matheus Hilliard; Massa, Isadora Morais; Carneiro, Maico Fernando Wilges; Pinheiro, Fernanda (Anais de Medicina Veterinária, 2022)
.